Theory Amid Policy and Practice: A Typology of Theory Use in Educational Leadership Scholarship. (March 2022) - Modeste, Marsha E.; Pavlakis, Alexandra E.; Nguyen, Chi
In the field of educational leadership, there is some work around the preferred theories of scholars, but little to no research on how the chosen theories are subsequently applied. Better understanding the purpose, role, and depth of how theory is used in educational leadership can help inform the teaching and mentorship of aspiring leaders and scholars. To examine the nature of theory use in educational leadership, we applied Dressman's typology of theory use in literacy (2007), to 47 policy and practice-oriented articles in Educational Administration Quarterly. We found similar patterns to Dressman's typology, but also important differences. Implications are discussed.